SPECTRUM OF HISTOPATHOLOGICAL PATTERNS OF DUODENAL BIOPSIES IN PATIENTS WITH UNEXPLAINED ANAEMIA AND CHRONIC DIARRHEA AND THEIR CORRELATION WITH ENDOSCOPIC FINDINGS AND SEROLOGICAL MARKERS - Yasin, Muhammad Awais; Farooq, Muhammad Asif; Uddin, Nasir; Parveen, Bushra; Asghar, Asma; Ahsan, Javeria (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate different histopathological patterns and correlate them with indications, findings of Esophagogastroduodenoscopy Esophago-gastro-duodenal (EGD) and serological markers in patients presenting of unexplained anemia and chronic diarrhea. Study Design: Cross sectional study. Place and Duration of Study: Departments of Pathology and Gastroenterology, Combined Military Hospital Lahore Pakistan, from Jul to Dec 2020. Methodology: Histopathological patterns of endoscopic duodenal biopsies, submitted for evaluation of unexplained anemia and chronic diarrhea were studied. Hemoglobin and anti-tTG levels were recorded. Adults with history of unexplained diarrhea and anaemia were included. Biopsies with malignant diagnosis or unfit for evaluation were excluded. Histopathological patterns were correlated with indications and findings of Esophagogastroduodenoscopy and serological markers of celiac disease. Results: The most common indication for Esophagogastroduodenoscopy in 145 patients was chronic diarrhea. Upper gastrointestinal endoscopy in 2/3rd of patients revealed no pathology. Histopathological patterns of duodenal biopsies revealed only 15% cases suggestive of celiac disease. Only 12 patients were suggestive of celiac disease both on Esophagogastroduodenoscopy and histopathology combined. Half of patients with anti tTG level >100 u/ml, showed histopathological features of celiac disease on. There was no correlation between histopathological patterns, indications of Esophagogastroduodenoscopy, morphology of Esophagogastroduodenoscopy and serological markers of celiac disease. Conclusion: Indications for Esophagogastroduodenoscopy, Esophagogastroduodenoscopic findings and histopathological patterns cannot diagnose celiac disease alone.